2012
DOI: 10.1111/j.1471-0528.2012.03407.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contraception provided at termination of pregnancy and incidence of subsequent termination of pregnancy

Abstract: Objective To determine the incidence of subsequent termination of pregnancy (TOP) within a 2-year period in relation to the method of contraception provided to women following the index TOP.Design Case note review.Setting NHS hospital TOP service, Edinburgh, UK.Population Nine hundred and eighty-six women requesting a TOP in 2008.Methods Case notes were reviewed to determine the contraception provided at index TOP and whether women had subsequent TOP at the same hospital within 2 years.Main outcome measures In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 11 publications
8
81
1
1
Order By: Relevance
“…The demographic characteristics of women participating in our survey were similar to that of previous studies of women attending for TOP in our region 10. In addition, our finding of 8% of women having previously used an IUD/IUS is in keeping with rates of uptake of intrauterine contraception in the UK 3.…”
Section: Discussionsupporting
confidence: 86%
“…The demographic characteristics of women participating in our survey were similar to that of previous studies of women attending for TOP in our region 10. In addition, our finding of 8% of women having previously used an IUD/IUS is in keeping with rates of uptake of intrauterine contraception in the UK 3.…”
Section: Discussionsupporting
confidence: 86%
“…[68] LARC use among these women appears more effective than short-acting contraception in reducing repeat pregnancies and abortions. [69,70] In a multi-country trial, insertion of the implant immediately post abortion led to higher LARC use and reduced repeat pregnancies compared with insertion at a planned follow-up visit. [71] Also, in a study in Ethiopia, implant insertion immediately post abortion resulted in >80% of women leaving the facility with a contraceptive method compared with 58% before the services began.…”
Section: Cmementioning
confidence: 99%
“…In contrast, studies with a small sample, as evidenced in the study in which one of the CTs reported only having one subject enrolled, may lead to bias in the representativeness of the analysis. Randomization of eligible participants in intervention or control groups is another important point in this type of study, since it is a way of guaranteeing the same chance of allocation for both groups (23)(24) .…”
Section: Discussionmentioning
confidence: 99%